1994
DOI: 10.1115/1.2919491
|View full text |Cite
|
Sign up to set email alerts
|

The Dual Inertia Operator and Its Application to Robot Dynamics

Abstract: The principle of transference states that when dual numbers replace real ones all laws of vector algebra, which describe the kinematics of rigid body with one point fixed, are also valid for motor algebra, which describes a free rigid body. No such direct extension exists, however, for dynamics. Rather, the inertia binor is used to obtain the dual momentum, from which the dual equations of motion are derived. This raises the dual dynamic equations to six dimensions, and in fact, does not act on the dual vector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…This paper expands, in its first part, the results reported in Brodsky and Shoham's paper [7] and gives a more general expression for the dynamic equations which enables the calculation of the dual momentum and the dual force with respect to an arbitrary point. Then, the moment-product is applied to obtain the energy of a rigid body.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…This paper expands, in its first part, the results reported in Brodsky and Shoham's paper [7] and gives a more general expression for the dynamic equations which enables the calculation of the dual momentum and the dual force with respect to an arbitrary point. Then, the moment-product is applied to obtain the energy of a rigid body.…”
Section: Introductionmentioning
confidence: 83%
“…Only recently, a new dual number formulation of a rigid body dynamics was suggested that casts the equations throughout the derivation into a three-dimensional form [7,32]. This approach is detailed in the next section.…”
Section: The Inertia Binor and Its Application To Rigid Body Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The derivation of the inverse dynamic equations of this robot requires the calculation of the Jacobian matrices to each one of the robot links center-of-mass. As mentioned above, (Section 2), the Jacobian matrix is obtained explicitly from the product of the dual transformation matrices, the third column of dual transformation matrix 3 A Ã 0 (rotation about z 0 ), the ®rst column of 3 A Ã 1 (rotation about x 1 ) and the second column of 3 A Ã 2 (translation along y 2 ):…”
Section: Illustrative Examplementioning
confidence: 99%
“…(6) in a form that includes also the dynamic loads. Using the virtual-work and D'Alembert principles [1] and applying the dual inertia operator [3] the following equation is obtained:…”
Section: Derivation Of the Jacobian Matrix From The Product Of Dual Omentioning
confidence: 99%